Perfil del adulto mayor del centro poblado Pacanguilla Chepén 2010 - Espinoza Sánchez, Julissa Donatilde (2010)
The present study of investigation of descriptive type of transverse court I realize, with the intention of determining the profile demographic: age, sex, degree of instruction, marital status, type of family; the profile of health: nutritional condition, mental condition, level of functional independence according to the basic and instrumental activities of the daily life; and social profile: social support, familiar functioning of the adult major population of the Populated Center Pacanguilla. The sample was constituted by 97 major adults selected according to criteria of incorporation established. The compilation of information was done by means of a personal interview. Using a due validated instrument, which three aspects approached: demographic profile, profile of health and social profile. Obtained the information they were tabulated using absolute and percentage frequencies. Of the obtained results it came near to the following conclusions: 1.-The major percentage (51,5 %) of older adults is between 60 to 69 years. The predominant sex in this population is the masculine one (58,8 %). 47,4 % has a degree of primary instruction and 39.2 % is illiterate. The predominant marital status is married one (33 %). The type of family of major frequency (44,3 %) is the nuclear family. 2.-The major percentage (84,5 %) of older adults presents a high nutritional risk. The majority of the elders (82,5 %) present a mental complete condition. 75,3 % of major adults is independent as for the basic AVD, and the major percentage 54,6 % is dependent in the instrumental AVD 3.-The major percentage 49,5 % of older adults presents social support moderately suitably and 34 % presents social suitable support. The major percentage 71,1 % of major adults presents a family normofuncionante.